Examples of heritage houses in Jubba city (Journal of the College of Education for Women, 2019)
The researcher tried to concentrate on the field study included many houses for the sake of documenting it by pictures and schemes with its history using the available data that had got from elderly whereas the rest of heritage will document in other research , in God willing .The research confined on the studying of examples heritage houses which was some of them had built at the end of 19th century AD but, other of them had built on the beginning of 20th century . In spite of considering these buildings are important and as a sign to architect art of Jubba but, there is never full studying written about them in Western city .The importance of this study lies on documenting sides of environmental and climatic progress which Iraqis had depended on to build houses according to this systems .The benefit of this study is to emphasize the identity of the Iraqi architecture its application intended to organize weather inside building blocks which were suitable to human’s nature in every season .